Facebook, selfies, una pizca de narcisismo y algo más… - González Sarmiento, Olga (2014)
This article analyzes the pervasiveness of the largest social network in theworld of relationships: Facebook. Review how users operate it; some,occasionally visiting it; other, making it an indispensable part of their livesand their way of presenting to the world. Aspects such as self-concept,self-esteem, narcissistic personality of the staunchest users features and, ofcourse, interpersonal relationships mediated by the network are explored.